Review and prospects of information technologies management in agriculture - N. M. Matsveichuk; Yu. N. Sotskov; A. Yu. Mikhailov (E-Management)
The paper presents research and review articles published between 2014 and 2023 on the use of cloud technologies and blockchain for smart agriculture development in Russia, China and the Republic of Belarus. The main directions of modern agriculture digitalization have been listed. The comparison of technical progress of agriculture in Russia and neighboring European countries (Poland and Latvia) has been carried out. The survey results show that in Russia advanced developments consider soil-climatic and agro-technological peculiarities of the territory, cloud technology providers and own data processing centers are being developed. Some practical systems are not unified, computing resources are geographically distributed, and less than 8–10 % of farms in Russia use digital platforms. Promising research directions of modern technologies and their application in agriculture have been described. The article studies information technologies used in intelligent agriculture based on cloud computing and blockchain. Intelligent agriculture is characterized by large amounts of data. Data transmission and analysis in such information system are based on cloud technologies. Agro-production processes are linked to other parts of the value chain in complex, highly automated production, and logistics chains involving wholesalers, retailers, logistics, agricultural producers, and their suppliers. Such chains can reduce food costs and retail prices, as well as the need for production and distribution capacity. Supply and value chains digitalization and digital platforms development that connect participants in the agroecosystem are driving the use of blockchain.